Antarctic surface hydrology and impacts on ice-sheet mass balance. Issue 12 (December 2018) - Bell, Robin; Banwell, Alison; Trusel, Luke; Kingslake, Jonathan
Abstract Melting is pervasive along the ice surrounding Antarctica. On the surface of the grounded ice sheet and floating ice shelves, extensive networks of lakes, streams and rivers both store and transport water. As melting increases with a warming climate, the surface hydrology of Antarctica in some regions could resemble Greenland's present-day ablation and percolation zones. Drawing on observations of widespread surface water in Antarctica and decades of study in Greenland, we consider three modes by which meltwater could impact Antarctic mass balance: increased runoff, meltwater injection to the bed and meltwater-induced ice-shelf fracture — all of which may contribute to future ice-sheet mass loss from Antarctica. With warming, meltwater will play an increasingly important role in driving ice loss from Antarctica, raising global sea levels. This Perspective discusses the key process through which Antarctic surface hydrology impacts mass balance.